Interlayers engineering for flexible large-area planar perovskite solar cells - Li, Jia (2020)
Hybrid metal halide perovskite solar cells (PSCs) have consistently demonstrated high power conversion efficiency (PCE), although the best performing PSCs mostly employ high-temperature (500 oC) processed compact and mesoporous TiO2. Instead, low-temperature processed PSCs are desirable for implementation on flexible substrates and tandem solar cells. Here, we present a new method to achieve high efficiency flexible planar PSCs based on a low-temperature processed nonaqueous sol-gel route synthesized TiO2 and a guanidinium iodide (GuaI) salt passivation treatment of the perovskite film. We fabricate both rigid and flexible triple-cation perovskite (Cs0.05 (MA0.17FA0.83)0.95Pb(I0.85Br0.15)3, Eg ~1.58 eV) PSCs, achieving PCEs of 19.8% and 17.0% on glass and polyethylene naphtholate, (PEN) substrates respectively. At the same time, rigid and flexible high-bandgap double cation (FA0.85Cs0.15Pb(I0.7Br0.3)3, Eg ~1.72 eV) PSCs reached a PCE of 18.0 % and of 15.8%. Moreover, large area (1cm2) ~1.58 eV and ~1.72 eV-PSCs achieved PCEs of 18.2% and 16.7% PCE on glass substrates and of 16.2% and 13.9% on PEN substrates demonstrating the high uniformity of all the solar cell layers.